Are the Central and Eastern European transition countries still vulnerable to a financial crisis? Results from the signals approach - Axel Brüggemann; Thomas Linne (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
The aim of paper is to analyse the vulnerability of the Central and Eastern European accession countries to the EU as well as that of Turkey and Russia to a financial crisis. Our methodology is an extension of the signals approach. We develop a composite indicator to measure the evolutin of of the risk potential in each country. Our findings show that crises in Central and Eastern Europe are caused by much the usual suspects s in others emerging markets. In particular an overvalued exchange rate. Weak exports and dwindling currency reserves have good precictive power for assessing crisis vulnerabilities.
URN:NBN:fi:bof-201605181127
Keywords: F31; F47; 330; financial crises; vulnerability indicator; Central and Eastern Europe